OP0104 Antibodies against carbamylated proteins are involved in osteoclastogenesis by inducing rankl expression in osteoblasts in vitro. (12th June 2018) - Spinelli, F.R.; Mancini, R.; Leopizzi, M.; Colasanti, T.; Pecani, A.; Ceccarelli, F.; Conti, F.; Valesini, G.; Alessandri, C.
Abstract : Burning bones Background: Citrullinated peptide are one of the main target of immune response in Rheumatoid Arthritis (RA) and antibodies to citrullinated peptides (ACPA) are involved in bone resorption. One of the target antigens – citrullinated vimentin – is expressed on the surface of osteoclast precursors where it can bind the antibodies starting the differentiation in mature osteoclast. Moreover, recent data demonstrated that serum levels of receptor activator of nuclear factor-κB ligand (RANKL) are higher in ACPA-positive RA patients. RANKL is the main osteoblast-derived cytokine inducing osteoclastogenesis. Antibodies directed against carbamylated proteins (Anti-CarP) have been recently described in RA patients with Rheumatoid Arthritis. The effect of anti-CarP on bone resorption has not been yet addressed. Objectives: The aim of the study was to investigate in vitro the effect of anti-CarP on Osteoprotegerin (OPG) and RANK ligand (RANKL) production in osteoblast cultures. Methods: Anti-CarP were investigated by ELISA in the sera of 88 RA patients using carbamylated fetal calf serum (CarFCS) and non-modified FCS as antigens. Anti-CarFCS were purified from the sera of 3 RA patients who tested highly positive for anti-CarP. Osteoblasts were isolated from the femoral head of 3 patients undergoing total hip arthroplasty and cultured in three different conditions – 1 ng/ml of anti-CarFCS, 10 ng/ml of anti-CarFCS or control medium for 4–6 days, until confluence. RNA was extracted from cell lysates and OPG and RANKL mRNA expression was analysed by Real-time PCR. Moreover, OPG and RANK expression was investigated by immunofluorescence on treated and non-treated cells. differences were determined either with two-way repeated measures analysis of variance (ANOVA) with Bonferroni's multiple comparison test, using Prism 5.0 software. A p value<0.05 was considered significant. Results: In osteoblast cultures, anti-CarFCS decreased the expression of OPG and increased the expression of RANKL in a dose-dependent manner, leading to an increase in RANKL/OPG ratio (figure 1A and 1B). The result was confirmed by the immunofluorescence analysis demonstrating the subcellular co-location of OPG and RANKL in osteoblast cultures (figure 1C). Conclusions: The results of the study confirm that anti-CarFCS can be detected in nearly 40% of RA patients. The increase of RANKL/OPG ratio in the osteoblast cultures treated with anti-CarFCS suggests an effect of such autoantibodies on osteoclastogenesis and osteoclasts activity, supporting their possible involvement in the development of bone erosions. Disclosure of Interest: None declared